Established and emerging prebiotics for gut microbiota - M. Veljković; A. Vukoičić; A. Petrov Ivanković; K. Banjanac (Microbiota in Health and Disease)
The concept of prebiotics was introduced more than two decades ago, but these bioactive molecules still represent an attractive area of research. This is due to their close connection with the intestinal microbiota and, consequently, of the entire human organism. Prebiotics are used as a food source by gut microbes, releasing various metabolites, of which short-chain fatty acids are key molecules in ensuring the normal functioning of the colon. Within the framework of this article, an overview of published scientific studies in the last year (from March 2023 to March 2024), on the impact on the intestinal microbiota residents of two groups of prebiotics (established and emerging), is given. The prebiotic effect of established prebiotics has been confirmed based on available in vitro and in vivo studies, while emerging prebiotics’ effect yet needs to be elucidated by in vivo studies. The available information shows novelties in the field of health benefits and modifications of established prebiotics, as well as the potential of many polyphenols and polysaccharides from different natural sources to exhibit prebiotic activity. Presented data give insight into the effect of prebiotics on beneficial and pathogenic microbes, and potential effective solutions for preserving health and suppressing diseases. A detailed analysis of the latest scientific publications in this field is of great importance for the food, confectionery, pharmaceutical and other industries that use prebiotics as an integral part of their products, to improve the quality of existing ones or to develop new ones.